2017
DOI: 10.1111/exd.13389
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CARD9‐mediated signalling to wound healing in skin

Abstract: The inflammatory response after skin injury involves the secretion of a variety of cytokines and growth factors that are necessary for tissue repair. Caspase recruitment domain-containing protein 9 (CARD9) is an essential signalling adaptor molecule for NF-κB activation upon triggering through C-type lectin receptors (CLRs), which are expressed in macrophages and dendritic cells. However, the role of CARD9 in inflammatory responses at the wound site has not been elucidated. In this study, we analysed the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(57 reference statements)
0
13
0
1
Order By: Relevance
“…The cellular and molecular pathways related to CARD9 signaling in the skin have been scarcely investigated ( 131 , 132 ) and it is currently unknown how CARD9 precisely drives cutaneous antifungal immunity ( Figure 2 ). The accumulating evidence in humans has shown, so far, that susceptibility to fungal diseases in CARD9-deficient patients is related to the poor production of inflammatory cytokines by myeloid cells in response to fungal antigens along with an impairment in type 17-mediated immunity ( 126 ).…”
Section: Inherited Card9 Deficiency and Deep Dermatophytosismentioning
confidence: 99%
“…The cellular and molecular pathways related to CARD9 signaling in the skin have been scarcely investigated ( 131 , 132 ) and it is currently unknown how CARD9 precisely drives cutaneous antifungal immunity ( Figure 2 ). The accumulating evidence in humans has shown, so far, that susceptibility to fungal diseases in CARD9-deficient patients is related to the poor production of inflammatory cytokines by myeloid cells in response to fungal antigens along with an impairment in type 17-mediated immunity ( 126 ).…”
Section: Inherited Card9 Deficiency and Deep Dermatophytosismentioning
confidence: 99%
“…Previously, we showed that CLRs-CARD9emediated signaling is involved in wound healing (Kanno et al, 2017). Therefore, to identify the possible contribution of dectin-2, the expression of dectin-2 mRNA was examined.…”
Section: Increase Of Dectin-2 Expression In Skin After Woundingmentioning
confidence: 99%
“…It has been reported that deficiency of TLR2 (Dasu and Isseroff, 2012), TLR4 (Chen et al, 2013), TLR9 (Sato et al, 2010), or MyD88 (Macedo et al, 2007) leads to attenuated wound healing in skin. As for the role of CLRs, we recently showed that CARD9, an essential signaling adaptor molecule through CLRs, plays a key role in the wound healing process (Kanno et al, 2017). Additionally, dectin-1 ligand b-1,3-D-glucan was reported to improve wound healing (Roy et al, 2011;van den Berg et al, 2014), whereas its role in other CLRs is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Recruited neutrophils and macrophages release additional chemokines, such as CCL3, to enhance migration of inflammatory cells to the wound that release pro-angiogenic growth factors, which are important for neovascularization [ 7 ]. High expression levels of CCL3 has been linked with enhanced wound healing [ 43 , 44 , 45 ]. In contrast to Collagen, HSH-Collagen showed a statistically significant rise in CX3CL1 transcripts.…”
Section: Discussionmentioning
confidence: 99%